Optimal Combination of Femoral Tunnel Orientation in Anterior Cruciate Ligament Reconstruction Using an Inside-out Femoral Technique Combined With an Anterolateral Extra-articular Reconstruction. Issue 5 (April 2022) - Stordeur, Alban; Grange, Sylvain; Servien, Elvire; Blache, Yoann; Klasan, Antonio; Putnis, Sven E.; Boyer, Bertrand; Farizon, Frédéric; Philippot, Rémi; Neri, Thomas
Background: The optimal orientation of the anterolateral extra-articular reconstruction (ALLR) femoral tunnel to avoid collision with the anterior cruciate ligament reconstruction (ACLR) femoral tunnel is not clearly defined in the literature. Purpose: To define the optimal combination of orientations of the ALLR femoral tunnel and the ACLR femoral tunnel using an inside-out technique to minimize risk of collision between these tunnels. Study Design: Descriptive laboratory study. Methods: Three-dimensional reconstruction of magnetic resonance imaging scans of 40 knees after an isolated ACLR with an inside-out femoral technique was used to assess the collision risk between ACLR and virtual ALLR tunnels. The optimal ACLR tunnel orientation was defined as having the safest distance from the ALLR tunnel. A second collision analysis was performed on all patients presenting with an optimal orientation of the ACLR tunnel to then define the optimal ALLR tunnel orientation. The potential for trochlear damage was also studied. A collision risk of 0% to 5% was considered acceptable and referred to as "low risk." Results: The only ALLR tunnel orientation presenting a low risk of collision with the ACLR tunnel was with an axial angle of 40° anteriorly and a coronal angle of 0°. This orientation presented a 48% risk of trochlear damage with the guide wire of the ALLR tunnel. The more posterior the orientation of the ACLR, the larger the distance from the ALLR tunnel. Among the 22 patients presenting with an optimal ACLR tunnel (alpha angle superior to 40°), the ALLR tunnels aimed with 1 of these 3 orientations presented a low risk of tunnel collision and trochlear damage: 40° axial and 10° coronal, 35° axial and 5° coronal, or 30° axial and 0° coronal. Conclusion/Clinical Relevance: To minimize risk of tunnel collision or trochlear damage when combining an inside-out ACLR with an ALLR, the ACLR tunnel should be performed with a posterior orientation (alpha angle >40°), and the ALLR tunnel should be aimed with 1 of 3 orientations: 40° axial and 10° coronal, 35° axial and 5° coronal, or 30° axial and 0° coronal.